The effects of passive blinking on exposure keratopathy among patients in intensive care units - Korosh Rezaei; Nazanin Amini; Reza Rezaei; Fatemeh Rafiei; Mehdi Harorani (Wolters Kluwer Medknow Publications, 2022)
Background: Patients in Intensive Care Units (ICUs) are at risk of eye disorders such as Exposure keratopathy (EK) due to impaired blinking and incomplete eye closure. The aim of this study was to assess the effects of passive blinking exercise (PBE) on EK among patients in ICUs. Materials and Methods: This single-blind, randomized, clinical trial was conducted in 2017. The study participants included 51 patients purposively recruited from the three ICUs of Valiasr Teaching Hospital, Arak, Iran. Through coin tossing, one eye of each participant was randomly allocated to the intervention group and the other to the control group. The eye in the control group received routine eye care, whereas the eye in the intervention group received routine eye care and PBE for a week. EK prevalence and severity were assessed daily for 7 consecutive days using fluorescein eye staining papers and an ophthalmoscope with a cobalt blue filter. Results: The study groups did not significantly differ from each other in terms of the baseline prevalence and severity of EK. After the intervention, the prevalence of EK (χ2 = 13.44, df = 1, p < 0.001) and the prevalence of grade II EK (χ2 = 8.33, df = 1, p = 0.003) in the intervention group were significantly lower than the control group. Conclusions: PBE is effective in significantly reducing EK prevalence and severity among patients in ICUs. Therefore, critical care nurses are recommended to use PBE for EK prevention and management.